Information management design for higher education - Fajriyah, Annisa; Mudawamah, Nita Siti; Puspitadewi, Ganis Chandra (Record and Library Journal, 2024)
Background of the study: The existence of information management unit is important for the continuity of information life cycle. However, in reality, not all institutions have this unit. This research was conducted to provide an overview of information management at universities that do not yet have a special information management unit. Purpose: This research aims to provide a design information management that can be applied, especially at the UIN Malang or other public universities; especially those that have similar conditions with this university. Method: This study utilized a qualitative method and a case study approach. Through in-depth interviews with parties who understand the flow of the university's work. In addition, observations were conducted at other institutions with comparable structures to develop a workable information management design for this institution. Findings: An information management design at Universitas Islam Negeri Malang can be implemented with policies and division of work in certain units owned by this university. Conclusion: A workflow, especially for information management, must be implemented with commitment from all units involved, so that the absence of a related unit does not become a barrier to information management.